THE USE OF WHATSAPP APPLICATION TO TEACH WRITING OF RECOUNT TEXT - Dumanauw, Asiani; Sutapa Y, Y Gatot; Salam, Urai (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis is a study on increasing students? skill of writing recount text through the use of WhatsApp on the tenth-grade students of SMA Negeri 5 Pontianak in academic year 2018/2019. The method implemented in this research was Pre-Experimental research with single group pre-test and post-test design. The subjects of the research were 35 students of class X IPA 1, the writer took the sample by using cluster random sampling. The data were collected through written test. Referring to the research findings, it was showed that the use of WhatsApp gave a positive contribution to the students? writing achievement of recount text. The use of WhatsApp to teach writing of recount text is succeeded in increasing students? writing achievement of recount text. Thus, the writer recommends the teacher to use WhatsApp in teaching learning process, to not only teach writing but also speaking, reading, and listening.Key Words: Writing, Recount Text, WhatsApp.